Rurification of Religion. Foci and Suggrundaria at the Roman Vicus of Falacrinae (Cittareale, Rieti, Italy) - Gasparini, Valentino (ARYS. Antigüedad: Religiones y Sociedades, 2021)
The results of the archaeological exploration of the Roman vicus of Falacrinae, placed in the Upper Sabina 78 miles north-east of Rome, represent excellent first-hand material for testing the concept of “rurification” of religion. The frequentation of the area goes back over time at least to the late Neolithic, but it is only in the Archaic period that a temple was built, soon converting itself into a sort of pole of attraction of the local community. After the Roman conquest (290 BCE), an entire village gradually arose around the monument. 129 sacrificial foci, dated between the late 3rd and the second half of the 1st cent. BCE (probably linked with the festivals of the Feriae Sementivae, Paganalia or Compitalia), and few burials (suggrundaria) belonging to perinatal foetuses of 30/40 weeks of gestation, dated during the 2nd and the first half of the 1st cent. BCE, are the most intriguing ritual practices that the excavations have been able to identify. The analysis of these practices encourages to conclude that the local rural communities: 1) adopted group-styles of religious grouping significantly different from those taking place in urban contexts; 2) could strongly modify hierarchies and rituals performed in the cities; 3) cannot necessarily be considered as “deviant” from the normative point of view; 4) could easily negotiate between local religious traditions and urban patterns.